Strong convergence of modified Halpern iterations in CAT(0) spaces - Panyanak B. (2014)
Strong convergence theorems are established for the modified Halpern iterations of nonexpansive mappings in CAT(0) spaces. Our results extend and improve the recent ones announced by Kim and Xu (2005), Hu (2008), Song and Chen (2008), Saejung (2010), and many others. Copyright 2011 A. Cuntavepanit and B. Panyanak.